ANALISIS PENERAPAN PROJECT MANAGEMENT LIFE CYCLE PADA PROGRAM PENGEMBANGAN KOMPETENSI DIGITAL - Prety Diawati; Dwi Aprilya Sari (LAND JOURNAL, 2026)
The rapid development of digital transformation encourages organizations to implement project management systematically to ensure projects are executed effectively and efficiently. This study aims to analyze the implementation of project management in a corporate digital competency development program, identify obstacles encountered during project execution, and examine the efforts undertaken to address those obstacles. This research employed a qualitative descriptive approach. Primary data were collected through observations, interviews with individuals involved in program implementation, and documentation, while secondary data were obtained from published company documents and relevant literature. The collected data were analyzed using the Miles, Huberman, and Saldana qualitative analysis model, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that the organization has implemented the five stages of the Project Management Life Cycle, namely initiation, planning, execution, monitoring and controlling, and closing. However, several challenges were identified, including adjustments to planning, changes in resource allocation, suboptimal risk management, and limited utilization of evaluation results as a basis for continuous improvement. The study concludes that project management has provided a structured framework for program implementation, yet its effectiveness can be enhanced through better planning, early risk identification, strengthened monitoring and controlling processes, and continuous evaluation to improve future project performance